Cyberspace Security : Reading in the Legal Concept - Abbas, Mohammed; Hamza, Waleed (Journal of Legal Sciences, 2023)
After the tremendous development witnessed by the world of communications at the beginning of the third millennium, the activities that are performed through cyberspace have increased, and its importance has therefore increased, and the risks to which this space is exposed have increased, and in view of the global trend towards regulating this space and the practices that take place through it, as well as finding legal and technical ways to secure it. And to secure the services that are provided through it, it was necessary to determine the nature of this space and therefore its security. In order to create an appropriate theoretical framework around it that may be used if the Iraqi legislator goes towards organizing this space and securing it legislatively.